Rhetorical image and its effectiveness in forming the poetic image (Ibn al-Wardi is an example) (Journal of Hama University, 2025)
The research represents a serious attempt to study the graphic image according to Ibn al-Wardi, given its importance as a basic element of the formation of the poetic image. It is like the vital fabric on which the image in poetry is built, and its  presence in it is an important pillar. Because it represents the content of the image, it also gives the text beauty and the content majesty and depth in the process of artistic and aesthetic appreciation, behind which lies the true essence of the image,  Form and content work side by side to crystallize and embody it in its final form, the research will address the three forms graphic images: simile, metaphor, metonymy, it will also explain the mechanism used in the work of each of them with an explanation of the functional role it plays in supplementing the poetic image, in addition to showing the significance of the image to reveal the poets vision.